Mental, neurological and substance use disorders among the Latino migrant population in the United States who visited the Health Windows and Mobile Health Units in 2021 - López Jaramillo, Ana María; Rangel Gómez, María Gudelia; Morales Chainé, Silvia; López Montoya, Alejandra; Lira Chávez, Isaura Angélica; Cruz-Piñeiro, Rodolfo (Frontiers in Public Health, 2023)
Mental health is defined by the WHO as a state of well-being in which people are aware of their own abilities to cope with the normal stresses of life, work productively and fruitfully, and contribute to their community. Among the minority groups that may be vulnerable to experiencing greater risks for their physical and mental health and full development is the migrant population. The migration experience to which the mobile population is exposed is associated with upheavals that translate into psychosocial problems and stressful conditions one would expect to be resolved using certain coping strategies. To describe the sociodemographic profile of the Latino migrant population in the USA who visited HW and MHU in 2021, who may have been at risk for mental, neurological or substance use disorders. People treated at HW and MHU were offered preventive services and underwent mental health screening. If their results showed signs and symptoms of mental health conditions, they were screened by professionals from the Psychology Faculty of the National Autonomous University of Mexico so they could be given a diagnosis and specialized care remotely and/or online with MHU and HW network partners. Approximately 2% of those who visited HW underwent the My health is also mental screening together with 1.2% of those who were attended at MHU. The highest concentration of migrant population who screened positive for mental health disorders corresponded to female population, with 71% in HW and 69% in MHU. Among migrants who visited HW, a third of both male and female population reported having experienced at least one mental health risk or problem in 2021. A calculation of average scores to define the proportion of the population with health disorders or problems showed that in the case of HW, a fifth reported experiencing at least one risk symptom. In MHU, this percentage rose to 41%. Across all the age groups in the migrant population attended, the most recurrent symptoms were associated with depression, anxiety, and experiences of psychosis. At the same time, women and the youth population have been at the greatest risk for mental health and substance use disorders.